Cost Benefit Analysis Taman Kuliner Condongcatur, Depok, Sleman, Yogyakarta - Mutmainah, Nur Fitri (Jurnal Ilmiah Administrasi Publik, 2016)
This article describes about Benefit Cost Analysis development of Taman Kuliner Condongcatur. It was found that there are three actors performing important roles in the development of Taman KulinerCondongcatur: Sleman regency government, stall tenants, and people surround the court. Of the actors, there was benefit cost which was spent and received as the consequence of Taman Kuliner. The cost and benefit earned by both Sleman Regency and the tenants were far from expectation. The net benefit cost received by Sleman regency government was negative Rp. 271.670.000,-. The net benefit cost received by stall tenants was positive Rp. 57.684.000,-. The indirect cost which cannot be measured with money was the people’s losing job. The indirect benefits were labor force absorption and the availability of means and infrastructures of art and socio-cultural performance to the society.